Nineteenth century communications
1 online resource
Keywords: "This four-volume collection contextualises primary sources related to nineteenth-century communications, including periodical articles, institutional and administrative records, material artefacts, and manuscript material such as correspondence, minutes, and memoirs. The collections contributes to improving understandings of how nineteenth-century, especially Victorian, communication media, infrastructure, and technology have shaped the globalised, networked world in which we live today"-- Provided by publisher.